2012
DOI: 10.1098/rspa.2012.0053
|View full text |Cite
|
Sign up to set email alerts
|

The use of acoustic inversion to estimate the bubble size distribution in pipelines

Abstract: The most popular technique for estimating the gas bubble size distribution (BSD) in liquids is through the inversion of measured attenuation and/or sound speed of a travelling wave. The model inherent in such inversions never exactly matches the conditions of the measurement, and the size of the resulting error (which could well be small in quasi-free field conditions) cannot be quantified if only a free field code exists. Users may be unaware of errors because, with sufficient regularization, such inversions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Humans have spent over a century researching this interaction for a range of applications (Ainslie, Leighton, 2009). These include attempts to derive beneficial effects from bubble acoustics, in fields as diverse as: climate science for air/sea transfer (Thorpe, 1992 ; the processing and monitoring of pharmaceuticals and food (Campbell, Mougeot, 1999;Skumiel et al, 2013), and of fuel and coolant (Leighton et al, 2012a); the generation of microfluidic devices (Carugo et al, 2011); ultrasonic cleaning (Leighton et al, 2005;Offin et al, 2014); and, in biomedicine, the provision of acoustic contrast agents and drug delivery vectors (Ferrara et al, 2007), and the use of cavitation as a therapy monitor (McLaughlan et al, 2010;Leighton et al, 2008a). Studies also include attempts to mitigate or exploit the detrimental effects of bubbles, for example in the cavitation erosion of turbines and propellers Szantyr, Koronowicz, 2006), ship noise and its environmental impact (Kozaczka, Grelowska, 2004;Parks et al, 2007;Grelowska et al, 2013), and the sonar clutter that oceanic bubbles can produce.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have spent over a century researching this interaction for a range of applications (Ainslie, Leighton, 2009). These include attempts to derive beneficial effects from bubble acoustics, in fields as diverse as: climate science for air/sea transfer (Thorpe, 1992 ; the processing and monitoring of pharmaceuticals and food (Campbell, Mougeot, 1999;Skumiel et al, 2013), and of fuel and coolant (Leighton et al, 2012a); the generation of microfluidic devices (Carugo et al, 2011); ultrasonic cleaning (Leighton et al, 2005;Offin et al, 2014); and, in biomedicine, the provision of acoustic contrast agents and drug delivery vectors (Ferrara et al, 2007), and the use of cavitation as a therapy monitor (McLaughlan et al, 2010;Leighton et al, 2008a). Studies also include attempts to mitigate or exploit the detrimental effects of bubbles, for example in the cavitation erosion of turbines and propellers Szantyr, Koronowicz, 2006), ship noise and its environmental impact (Kozaczka, Grelowska, 2004;Parks et al, 2007;Grelowska et al, 2013), and the sonar clutter that oceanic bubbles can produce.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the liquid and pipe are acoustically coupled 20,21 and because, over most of the frequency range of interest in some pipe systems (such as SNS), modal acoustic propagation occurs with distinct frequencydependent sound speeds and attenuations for each mode. The current authors 10 showed that errors of þ/À 1000% can occur when such an approach is followed in a pipe of similar dimension to that used in the SNS at Oak Ridge National Laboratory (ORNL). Further complications occur with the acoustic inversion techniques that are based on the bubble pulsation resonance since the pipe can alter the inertia, 17,[22][23][24] frequency, 25 and damping 26 of that bubble resonance.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, detectors for helium bubbles in steel pipelines filled with liquid mercury have been investigated for a spallation neutron source (SNS). [8][9][10] The ability to control the bubble size distribution, and to generate and detect a broad range of acoustic frequencies with controlled and calibrated amplitude in order to measure the bubble population, is however more characteristic of the laboratory than of industry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations